Increased Circulating T Follicular Helper Cells Induced via IL-12/21 in Patients With Acute on Chronic Hepatitis B Liver Failure - Du, Bingying; Teng, Jiaming; Yin, Rongkun; Tian, Yuanyuan; Jiang, Tingwang; Du, Yanan; Cai, Wei (Frontiers in Immunology, 2021)
Objectives: T Follicular helper (Tfh) cells, recognized as a distinct CD4+ T cell subset, mediate the development of long-lived humoral immunity via B cell activation/differentiation. Tfh cells play an important role during hepatic viral infection, but its role in hepatitis B virus-related acute on chronic liver failure (HBV-ACLF) remains to be explored. Materials and methods: The frequency of Tfh cells, serum pro-inflammatory cytokine (IL-12, IL-21, IL-17 and TNF) levels and IgG/M levels were investigated in HBV-ACLF (n = 36), serious chronic hepatitis B (n = 21), moderate chronic hepatitis B patients (n = 32) and healthy control (HC) subjects (n = 10). Results: Circulating Tfh cells were significantly increased in HBV-ACLF patients compared to other groups, correlating well with MELD score. However, the frequency of Tfh cells decreased in ameliorated HBV-ACLF patients. Furthermore, serum IL-12 and IL-21 levels were higher in HBV-ACLF patients, compared to other groups. Naïve CD4+ T cells from HC subjects differentiate into Tfh cells following treatment with HBV-ACLF patients’ serum, a process which can be blocked by IL-12/21 neutralizing antibodies. Tfh cells induced by HBV-ACLF patients serum promoted the proliferation and IgG production of B cells in vitro. Moreover, circulating CD19+ B cells, serum and liver IgG/M levels were significantly higher in HBV-ACLF patients, compared to other groups. Conclusions: Our data demonstrated that there was a high frequency of Tfh cells and high levels of serum IL-12/21 in HBV-ACLF patients. Naïve CD4+ T cells differentiate into Tfh cells in the presence of HBV-ACLF patients’ serum rich in IL-12/21, which can be blocked by neutralizing IL-12/21 antibodies. These data may provide useful insights for both clinical and basic research in the treatment of HBV-ACLF.